Simultaneous bladder rupture with obstetrics anal sphincter injury following forceps application: a case report and review of literature - Mahapatra, Kishore Chandra; Dora, Santosh Kumar; Dandapat, Atal Bihari; Naik, Bulu; Dash, Debashish; Karanth, Snehadarshini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
In the modern era use of instrumental delivery is on a declining trend. Due to increase morbidity associated with forcep applications most women in developing countries preferred emergency caesarean section over instrumental delivery. But in country like India instrumental delivery is still preferable over caesarean section in many situations. We report a case that was referred from a peripheral hospital with simultaneous bladder and anal sphincter injury to our hospital. She was managed by a multidisciplinary team including urologist, surgeon and gynaecologist. Such type of case is very rare in modern era. To prevent such complications prerequisite for forcep application must be fulfilled. So that bladder injury, urinary fistula, anal incontinence and fetal complication can be avoided.